The Correlation of Perceived Social Support with Suicidal Ideation through Loneliness as a Mediator in University Students - Siahaan, Lydia Julyeta; Scarvanovi, Berliana Widi (Universitas Islam Indonesia, 2024)
On an annual basis, the rate of suicide cases among university students have been observed to experience a significant increase. A significant reason observed to be predominantly responsible for suicidal incidents is loneliness, and perceived social support is an effort renowned to reduce these feelings among university students. Therefore, this study aimed to thoroughly analyze the relationship between perceived social support and suicidal ideation in university students, with loneliness serving as the mediating variable. In order to achieve the stated objective, 395 respondents aged 18-24, who were engaged in a dating relationship or have a best friend, were selected using a purposive sampling technique. Accordingly, three scales were used in the analysis namely the suicidal ideation, the perceived social support, and the loneliness scales. The obtained results showed that a direct relationship exist between perceived social support and suicidal ideation. It is also important to state that the mediation effect through loneliness was found to be greater than the direct effect (-.4676 > -.225), indicating partial mediation. Based on the observations, it was suggested that enhancing perceived social support while reducing loneliness can play an important role in preventing suicidal ideation, particularly among university students. This study emphasizes the importance of fostering supportive environments and addressing loneliness to mitigate the risk of suicide among this vulnerable population.